Response of upland rice cultivars to nitrogen fertilizer in the savannas of Nigeria - Kamara, A.Y.; Ekeleme, F.; Omoigui, L.O.; Oikeh, S.O.; Chikoye, David; Tegbaru, A. (2010)
In the dry savannas of West Africa, cultivation of upland rice (Oryza spp.) under rain-fed conditions is expanding due to the introduction of the New Rice for Africa (NERICA; WARDA, Bouake, Cote d'Ivoire) but appropriate N recommendations for these new cultivars are lacking. The present study evaluated the response of four NERICA rice cultivars, their parents (WAB 56-104 (O. sativa, tropical japonica type), CG 14 [O. glaberrima]) to four rates of N (0, 30, 60, and 90 kg ha−1) at Sabon-Gari (Sudan savanna, SS) and Tilla (northern Guinea savanna, NGS) in 2007 and 2008. There was no interaction between N rates and rice cultivars for grain yield, suggesting that the rice cultivars responded similarly to N application. Grain yield of NERICA rice cultivars responded significantly to N application in the Nigerian dry savannas following a linear response, even at 90 kg N ha−1, thus optimum rate might be above this N level. NERICA 1, NERICA 3, and NERICA 4 had comparable yields and produced 1.4 to 1.7 times more grains than the other cultivars in Sabon-Gari; while in Tilla, NERICA 4 and WAB56-104 produced the highest yield. NERICA 1, NERICA 3, and NERICA 4 may be more suitable for cultivation in Sabon-Gari (SS) while NERICA 4 and WAB56-104 can be recommended for Tilla (NGS).